School Mid-Day Meal Program in India: Past, Present, and Future - SHARMA, DR. MEENAKSHI (The journal of contemporary issues in business and government, 2021)
In 1995 the National Primary Education Nutrition Support Program was launched with two main objectives: Universalization of elementary education and enhancement of primary school student's nutritional status. The dominant government offered 100 g of wheat / rice per day to children in classes I to V throughout the province, local authorities and the Government helped the elementary schools. Hot cooked meals were provided by Kerala, Orissa, Tamil Nadu, Chhattisgarh and MP Cereals providing but other states and UTs provided 3 kg of cereals / month to 80 percent attendance for children. By 2001 there were more than 100 systems had served millions of students in 7, 92,000 colleges. In 2001, India's Supreme Court governed that midday meal (MDM) is a legitimate claim for school children, and also that the administration would have to deliver all primary school children with a hot cooked midday meal for 200 days. Universal primary schooling and MDM have also been accomplished in the last decade. MDM provides roughly 100 million children with hot cooked meals each day. MDM’s cereal content is sufficient but MDM’s pulse but vegetable quality is insufficient. Under-nourished school health facilities in coordination with MDM can be identified; Usage of the Body Mass Index (BMI) for aged for healthy and over-nourished children, as well as provide adequate therapy and treatment. If this method is implemented and regularly practiced, and the nutritional child is diagnosed can be considerably improved.